Futures Contracts in Islamic Finance: An Analytical Approach - Muhammad Asif Ehsan (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2013)
Futures contracts provide a useful means of reducing risk because these are highly liquid instruments that can be entered into or liquidated at any time. However, the debate on the legitimacy or otherwise of these contracts in the Islamic commercial law continues to invoke different contentions. The paper accentuates the fact that futures contracts are at bottom a new phenomenon of this age which have no precedent or parallel in the conventional law of transactions (muamalat). Therefore their legality or otherwise should be looked into with the Islamic viewpoint of general permissibility in relation to transactions. The paper examines a number of jurisprudential and legal issues such as non-existence of the subject-matter, sale prior to taking possession, bai al-kali bil-kali, speculation and hedging, and concludes that futures contracts are allowed to benefit from. However, only hedgers can take advantage of them. These instruments can never be used for purely speculative purposes where making or taking delivery is not intended. Although it is not necessary to pay the complete price to the seller at the time of the contract yet some other precautionary measures such as a bank guarantee or a fair amount of money to be given to the seller should be taken to ensure that pure speculation is scrupulously forestalled and the delivery would certainly be made.